Dengue, Chikungunya, and Zika: Differences in Similarities - Sutiono, Dias Rima; Gunawan, Jeremy David (Cermin Dunia Kedokteran, 2017)
Arbovirus (arthropod-borne virus) outbreaks have become a major problem in recent decades. Dengue, Chikungunya, and Zika outbreaks are part of the main focus currently as they share similar vector, symptoms, and environment. Reported cases of these viruses have occurred in epidemic areas with low mortality rate at the same time. This condition complicates diagnosis. Despite those similarities, each virus has their unique viral characteristics, transmission, symptoms, and complications. These unique characteristics can improve understanding of the diseases and be used to prevent and to diagnose the disease.Arbovirus (virus arthropoda-borne) merupakan wabah yang menjadi masalah besar dalam beberapa dekade terakhir. Wabah Dengue, Chikungunya, dan Zika termasuk fokus utama saat ini, karena memiliki vektor, gejala, dan lingkungan yang sama. Kasus di daerah epidemi dengan angka kematian rendah dilaporkan pada saat yang sama, kondisi ini mempersulit diagnosis penyakit. Meskipun mempunyai kesamaan, masing-masing virus memiliki karakteristik, transmisi, gejala, dan komplikasi yang unik. Karakteristik tersebut dapat digunakan untuk diagnosis, serta dapat meningkatkan pemahaman tentang penyakit dan cara-cara pencegahannya.